TI_GERICHTE 16.2024.11 vom 5. April 2024 , Irricevibilità di un reclamo contro un decreto di stralcio per transazione - TI Tribunale d'appello (2024)
Irricevibilità di un reclamo contro un decreto di stralcio per transazione